1996
DOI: 10.2355/isijinternational.36.suppl_s219
|View full text |Cite
|
Sign up to set email alerts
|

Argon Bubbles in Slabs.

Abstract: The effect of applying an EMBR was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…Most particles are captured 1-3 m below the meniscus, independent of casting speed, 162,169) which corresponds to a specific distance through the strand thickness. 163) Often, inclusions concentrate at one-eighth to one-quarter of the thickness from the top of the inside radius surface, 112,140) in addition to the surfaces, as verified by AK Steel Middletown Works (Fig. 32).…”
Section: Caster Curvaturementioning
confidence: 99%
See 2 more Smart Citations
“…Most particles are captured 1-3 m below the meniscus, independent of casting speed, 162,169) which corresponds to a specific distance through the strand thickness. 163) Often, inclusions concentrate at one-eighth to one-quarter of the thickness from the top of the inside radius surface, 112,140) in addition to the surfaces, as verified by AK Steel Middletown Works (Fig. 32).…”
Section: Caster Curvaturementioning
confidence: 99%
“…153,159,162) Gas bubbles also capture inclusions as they flow in the mold. 163) Figure 29 shows a typical bubble coated with inclusion clusters. 153) A tremendous number of alumina particles can be captured by a single bubble, as shown in Fig.…”
Section: Argon Gas Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Abbel et al reported that large argon bubbles (diameter >0.5 mm) had a nonhomogeneous distribution in slab in respect width and depth based on radiographic method. 6) Miyake et al believed that the distribution of bubbles in slab depends on the steel grade, especially on the sulfur content based on study on Kakogawa Work; and the authors pointed that electromagnetic stirring in the mold (M-EMS) was effective for removing bubbles and reduce sliver defect. 7) In cold rolled IF steel, slivers and blow-holes were two main types of visual surface defects; generally, the defects were caused by argon bubbles or argon bubbles in combination with entrapped mould powder; the sliver defects had relationship with the argon bubbles containing the alumina clusters or mould slag.…”
Section: Introductionmentioning
confidence: 99%
“…This class of bubbles comprises only a small fraction of all bubbles present in a typical slab of IF-steel. 7,8) Some researchers stress the importance of hydrogen in steel production. [9][10][11][12] The hydrogen is presumed to enter the steel somewhere during downstream processing increasing the internal hydrogen pressure at defects present in the steel.…”
Section: Introductionmentioning
confidence: 99%